The Effect of Flipped Class with Project Based Learning Dimensions Assisted by Moodle Combined with Reading, Questioning and Answering (RQA) on 4C Skills - Tarigan, Christine Ulina; Tarigan, Wenny Pinta Litna (Bioedukasi: Jurnal Pendidikan Biologi, 2022)
This study was to find out the effects of flipped class with project-based learning (PjBL) dimensions assisted by Moodle combined with reading, questioning and answering (RQA) strategies on students’ 21st-century skills. The research was quasi-experimental with cluster random sampling technique. The sample was three classes of twelve graders at a private school. The first class applied flipped class with project-based learning assisted by Moodle combined with RQA. The second class applied flipped class learning assisted by Moodle without PjBL and RQA. And the control class applied conventional online learning using Moodle only. Each class consists of 25 students. The instrument was an essay test with 10 questions. The collaboration and communication skills were assessed using observation sheets. The average of these two values used as a reference to determine the predicate of students’ 4C ability. The normality and homogeneity tests found that the three classes were the same and normally distributed (sig.>0.05). The results of ANOVA test and student’s response observation showed significant differences in three classes S1, S2 and S3 (α = 0.05, sig.0.00). The first class shows the highest 4C skills results followed by the second and third treatment classes with average scores respectively 91.25; 91.52 (very competent), 83.32; 83.04 (very competent) and 73.74; 73.64 (competent). These findings were expected to be a recommendation for educators to integrate the 4C skills through flipped class to improve students’ skills.